Impact of CMMI-based process maturity levels on effort, productivity and diseconomy of scale - Alyahya, M.; Ahmad, R.; Lee, S.P. (2012)
The Software Capability Maturity Model Integration (CMMI) has become a popular Software Process Improvement (SPI) model for enhancing software development processes with the goal of developing high-quality software within budget and schedule. Since software development effort can be greatly affected by the organizational process maturity level, this study examines the impact of different CMMI-based process maturity levels on effort, productivity development team and diseconomy of scale for a standard project sizes. The COnstructive COst MOdel (COCOMO) is employed to compute the software development effort. The percentage of change (increase or decrease) in software development effort, productivity and diseconomy of scale is employed as a measure of effectiveness for this study. The results of this work demonstrate that each higher CMMI maturity level has a considerable impact in decreasing the development effort, increasing the productivity rate and reducing the diseconomy of scale. The results also indicate that the impact of CMMI-based maturity levels significantly increases with project sizes.